A preliminary study on a tooth preparation robot. (17th August 2020) - Yuan, Fusong; Lyu, Peijun
ABSTRACT: This is a study of a robot-controlled ultrashort pulse laser system used for tooth preparation to overcome drawbacks of traditional manual methods, thus improving its quality, precision, and clinical efficacy. Based on the international advanced digital technologies, automation technologies, and medical laser technologies, the entire tooth preparation process was completed autonomously using the robot-controlled ultrashort pulse laser. In the study, 15 extracted human first molars were prepared automatically by the robot system. And the result accuracy was evaluated using software. Compared with the CAD data of standard tooth preparation, the overall average error, preparation depth of the natural tooth preparation, and convergence angle were 0.05–0.17 mm, 2.097 ± 0.022 mm with an error of 0.097 ± 0.022 mm, and 6.98 ± 0.35° with an error of 0.98 ± 0.35°, respectively. The feasibility and accuracy of the robot-controlled femtosecond laser technique for tooth preparation were confirmed.